2014
DOI: 10.7860/jcdr/2014/7452.4390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slow and Fast Pranayama Training on Handgrip Strength and Endurance in Healthy Volunteers

Abstract: Background: Pranayama has been assigned very important role in yogic system of exercises and is said to be much more important than yogasanas for keeping sound health. Also different pranayamas produce divergent physiological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Increased HGS following ANB might be due to improved autonomic tone and hypo-metabolic state, which leads to increase the concentration on the task. [ 12 ] Decrease in elastic and viscous resistance of the lungs during inspiration increases respiratory muscle efficiency after ANB. It is known to increase the compliance by releasing surfactant and prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased HGS following ANB might be due to improved autonomic tone and hypo-metabolic state, which leads to increase the concentration on the task. [ 12 ] Decrease in elastic and viscous resistance of the lungs during inspiration increases respiratory muscle efficiency after ANB. It is known to increase the compliance by releasing surfactant and prostaglandins.…”
Section: Resultsmentioning
confidence: 99%
“…This fact was incorporated in development of pranayama, a technique of controlled breathing [ 10 ]. ANB is a simple technique, which was known to alter blood pressure, heart rate, respiratory rate, PEFR, muscle strength on acute exposure for about 15 minutes [ 9 , 11 , 12 ]. Hence it is of interest to assess the effects of alternate nostril breathing (ANB) on cardiorespiratory parameters and muscle strength among the rotating shift workers in the tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy University students, Anuloma-Viloma and Bhastrika Pranayama appear to be useful in enhancing physical health indices [28]. In addition, another study results showed that both slow and fast pranayamas for 12-weeks improve handgrip dynamometry characteristics, with fast pranayama being more effective than slow pranayama [29]. According to the literature, consistent hatha yoga practice can lead to enhancements in health-related aspects and could benefit to improve status of health and wellness [30].…”
Section: Discussionmentioning
confidence: 99%
“…The Copenhagen Stroke Study showed that 95% of stroke patients achieved the best neurological state in the 11th week after stroke, and patients with mild stroke showed quick recovery [18]. A literature review shows that yoga is widely used as an adjunctive treatment for hypertension and hand grip strength in the general population [19,20].…”
Section: Introductionmentioning
confidence: 99%